From The Magic Tree: The Wonders of Agarwood Leaves (Beverages for Healing Part 2) - Norul Amalina, Sabri (2017)
Like most people, I had my fair share of cluelessness when I first heard about Agarwood. Upon learning its sky high price, I was even more baffled! Then I started learning more about it and finally I have come to appreciate it. As the saying goes, you can’t love what you don’t know, right? Agarwood or Oud, as some might call it, actually refers to resinous wood of resin-producing trees native to the forests in South Asia and South East Asia. It has several other names but these two are probably closest to us in Asia.